(untitled) (Research, Society and Development, 2021)
That agriculture occurs in cities is a fact, but few studies have the purpose of understanding this phenomenon and its contributions to socio-environmental development. The objective was to analyze the contribution of urban agriculture to the sustainable development of cities and communities. The methodology consisted of analyzing scientific articles published in indexed journals, between the period of 2009 and 2019, which focused on the study of urban agriculture in Brazil. 667 articles were accessed, of which 40 met inclusion criteria. The selected studies involve 12 Brazilian states and 123 researchers. The results demonstrate that urban agriculture occurs in all regions of Brazil, has different multifunctional characteristics, plays an important role in maintaining agrobiodiversity and contributes to food and nutritional security. Furthermore, urban agriculture is an important component in the economic, social and ecological relations of cities and can generate benefits for urban spaces, promote health and assist in educational processes. We conclude that urban agriculture has the potential to be adopted as a strategy in the development of sustainable cities and communities.